Differentiation pattern in the use of space by males and females of two species of small mammals (Peromyscus difficilis and P. melanotis) in a temperate forest - De-La-Cruz, Ivan Mijail; Castro-Campillo, Alondra; Zavala-Hurtado, Alejandro; Salame-Méndez, Arturo; Ramírez-Pulido, José (THERYA, 2018)
The distribution patterns of individuals together with mechanisms that maintain them have significant implications for population-level processes. Sex-specific differences in home-range may strongly influence the spatial distribution of individuals, while the differential use of space by the sexes can yield insights into the mating system and the life history of the species. Sexual differences in the use of space could be due to different habitat requirements during the breeding season. This is interesting because the males and females likely are interacting with operational sex ratios and mating strategies. Here, we evaluated for ten months of the year 2014, the spatial patterns of ecological distribution in males and females of two species of deer mice (Peromyscus difficilis and P. melanotis) that coexist in a temperate forest. Also, we assessed the variation in the use of space by males and females in both Peromyscus species and we analyze the intensity of positive association or repulsion between males and females. During drought and rain seasons, males and females of both Peromyscus were captured. The sex and reproductive status of each were identified. To analyze the spatial patterns of ecological distribution, we used the Nearest Neighbor Analysis. Kernel spatial analysis was performed to evaluate the variation in the use of space of males and females between seasons. The Ripley’s K bivariate function was carried out to assess the positive association or repulsion between males and females in each season. We found a different use of space between sexes. Our evidence shed light on the respective life histories of these species and provides information on possible factors that they may be using to coexist successfully among them. We conclude that in this temperate coniferous forest: 1) use of space by P. difficilis and P. melanotis, is influenced by both sex and by the reproductive season, and that this pattern varies, according to shifts on ecological conditions that promote variation and availability of resources during the two pluvial seasons; 2) there are interspecific differences in the use of space with conspicuous intraspecific differences in females and males of P. difficilis (e. g., males are more territorial, and both sexes only become more clustered during the breeding season), while both sexes of P. melanotis are more gregarious; and 3) there is a clear differentiation in the reproductive seasons of both species that could be related to resources availability, such as shelters and food.